Analysis of Regional Expenditure, Regional Investment, and Labor Force Participation Rate on Environmentally Oriented Economic Growth in Malang City - Arif Nur Rahmadhon; Riniwati, Harsuko; Susilo; Setyowati, Peni Jati (Sekolah Pascasarjana Universitas Brawijaya, 2025)
This study aims to examine the influence of regional government expenditure, public investment, and labor force participation rate on environmentally oriented economic growth in Malang City. Employing a quantitative explanatory design, the research uses time-series data from 2010 to 2024 and applies multiple linear regression analysis. The results indicate that government expenditure and public investment have a significant impact on economic growth, whereas the labor force participation rate does not have a statistically significant impact. Moreover, the relationship between economic growth and the Environmental Quality Index (EQI) demonstrates a pattern consistent with the Environmental Kuznets Curve (EKC), where environmental degradation initially increases but later improves as income and environmental awareness rise. The study also reveals land cover changes due to urban expansion, highlighting the need for stronger spatial planning and the integration of Nature-Based Solutions (NBS) to promote sustainable development. The findings provide valuable insights into local policy strategies that strike a balance between economic progress and environmental preservation. Keywords: economic growth, environmental quality, government expenditure, investment, EKC